Handbook of research on developing sustainable value in economics, finance, and marketing - Akkucuk, Ulas 1975- (Business Science Reference, 2015)
"This book provides the latest empirical research findings on how sustainable development can work not just for organizations, but for the global economy as a whole, covering various fields, including economics, finance, and marketing; operations management; communication sciences; sociology; and information technology"-- Provided by publisher.